Additive Manufacturing of Stable Energy Storage Devices Using a Multinozzle Printing System. (6th December 2020) - Meng, Fanbo; Zhang, Mingchang; Huang, Jin; Lu, Wen Feng; Xue, Jun Min; Wang, Hao
Abstract: The development of the Internet of things has prompted an exponential increase in the demand for flexible, wearable devices, thereby posing new challenges to their integration and conformalization. Additive manufacturing facilitates the fabrication of complex parts via a single integrated process. Herein, the development of a multinozzle, multimaterial printing device is reported. This device accommodates the various characteristics of printing materials, ensures high‐capacity printing, and can accommodate a wide range of material viscosities from 0 to 1000 Cp. Complete capacitors, inclusive of the current collector, electrode, and electrolyte, can be printed without repeated clamping to complete the preheating, printing, and sintering processes. This method addresses the poor stability issue associated with printed electrode materials. Furthermore, after the intercalation of LiFePO4 with Na ions, X‐ray photoelectron spectroscopy and X‐ray diffraction results reveal that the Na ions permeate the interlayer structure of LiFePO4, enhancing the ion migration channels by increasing the ion transmission rate. A current rate of 2.5 mAh ensures >2000 charge/discharge cycles, while retaining a charge/discharge efficiency of 96% and a discharge capacity of 91.3 mAh g −1 . This manufacturing process can provide conformal power modules for a diverse range of portable devices with various shapes, improving space utilization. Abstract : This study details the development of a multinozzle multimaterial printing device, equipped with various types of nozzles depending on the characteristics of the materials. The additive manufacturing and customization of capacitors are realized, inclusive of the current collector, electrode, and electrolyte, can be printed in order, without requiring repeated clamping to complete the preheating, printing, and sintering processes.